Association of fecal zonulin and calprotectin levels with cardiovascular risk factors and target organ damage in a sample of patients with metabolic disorders - E. P. Kolesova; D. A. Usoltsev; E. V. Moguchaia; M. A. Boyarinova; A. M. Erina; K. M. Tolkunova; A. L. Maslyanskiy; A. V. Mazing; S. V. Kibkalo; E. Yu. Vasileva; N. S. Novikova; E. I. Ermolenko; et al. (Российский кардиологический журнал)
Surrogate markers quantifying the severity of intestinal inflammation (fecal calprotectin) and permeability (fecal zonulin) are currently considered nontraditional cardiovascular risk factors.Aim. To study the associations of fecal zonulin and calprotectin levels with cardiovascular risk factors and target organ damage among participants with metabolic disorders from a population sample of St. Petersburg residents aged 35-75 years.Material and methods. In-depth phenotyping was performed on patients from a cohort of St. Petersburg residents metabolic disorders (overweight, hyperglycemia) invited for reexamination as part of the ESSE-RF epidemiological study. All patients underwent a questionnaire examination (physical activity, smoking, alcohol consumption, sleep, stress, anxiety and depression, assessment of digestive system complaints, frequency of food consumption). In addition, blood pressure and pulse measurements, anthropometry, biochemical and hormonal blood tests, echocardiography, applanation tonometry, volume sphygmography, duplex carotid scanning, and determination of fecal zonulin and calprotectin levels were carried out.Results. The examined cohort (n=86; mean age, 56 [44,7;63,5] years; men, 49,5%) was characterized by a high prevalence of abdominal obesity (80,2%), dyslipidemia (low-density lipoproteins >3 mmol/l — 76,7%, triglycerides ³1,7 mmol/l — 43%, total cholesterol >4,9 mmol/l — 77,9%) and insulin resistance (64%) with slight sex differences. An increase in calprotectin occurs in 23,3% of patients, zonulin — in 30,3%, while an increase in calprotectin and/or zonulin occurs in almost half of those examined (47,7%). Fecal calprotectin levels are associated with indicators of dyslipidemia, obesity, inflammation and atherosclerotic vascular disease, as well as dietary patterns and socioeconomic indicators. Zonulin levels are associated with N-terminal probrain natriuretic peptide levels and the presence of vitamin D deficiency, gallbladder disease, and dietary patterns.Conclusion. Increase of at least one marker of intestinal permeability and inflammation occur in approximately half of the participants with metabolic disorders from a population sample of St. Petersburg residents. In addition to the association of calprotectin and zonulin with metabolic risk factors and dietary patterns, calprotectin levels were associated with atherosclerotic changes in the carotid arteries.